DAMPAK ORIENTASI BERBASIS STANDAR TERHADAP TUJUAN SPIRITUAL PENDIDIKAN ISLAM - Firdaus Amalia Sholehudin; Fika Anjana; Kharimah Yunisaputri; Intan Aprilia Putri; Rifqi Khairul Anam (Makkah: Journal Of Islamic Studies, 2026)
The standard-based curriculum has been widely implemented to improve educational quality, accountability, and effectiveness through measurable learning outcomes. However, within the context of Islamic education, this orientation presents challenges because the primary objective of education extends beyond academic competence to include the development of faith, piety, noble character, and students' spiritual awareness. This study aims to analyze the characteristics of the standard-based curriculum, examine its impact on the spiritual objectives of Islamic education, and formulate an integrative perspective for curriculum development. The research employed a qualitative approach using a library research method. Data were collected from books, national and international journal articles, and educational policy documents, and analyzed through content analysis. The findings indicate that a standard-based curriculum contributes positively to improving instructional quality, educational planning, assessment, and institutional accountability. Nevertheless, an excessive emphasis on achieving academic standards tends to reduce attention to the internalization of spiritual values, character formation, and moral development. Therefore, Islamic education curriculum development should adopt an integrative approach that balances academic competency with spiritual formation through effective learning strategies, habituation, exemplary practices, and comprehensive assessment systems. Such an approach is expected to produce graduates who are not only academically competent but also possess strong spiritual values and Islamic character.